The Effect of Predictable and Unpredictable Training Methods On The Reaction Speed of Futsal Goalkeepers (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of predictable and unpredictable training methods on the reaction speed of futsal goalkeepers. Reaction speed is an important ability for a goalkeeper in responding to fast and dynamic game situations. This study uses a quantitative method with a quasi-experimental design of the pretest-posttest control group design. The subject of the study consisted of 45 goalkeepers who were divided into three groups, namely the predictable training group, the unpredictable training group, and the control group. The measurement instrument used was the Hand Touch Reaction Test to measure reaction speed. The training program was carried out for 4 weeks with a total of 12 training sessions. The result showed that there was a significant effect between the predictable and unpredictable training methods on increasing the reaction speed of a futsal goalkeeper. The One-Way ANOVA test showed a significant difference between the three groups. Training with the unpredictable methods resulted in a higher increase in reaction speed compared to the predictable method and the conventional method. The results of the Bonferroni further test confirmed that there was a significant difference between the unpredictable and predictable groups (p = 0.013) and with the control group (p